2012
DOI: 10.1038/ki.2011.448
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNAs in kidney homeostasis and disease

Abstract: MicroRNAs (miRNAs) are endogenous short (20-22 nucleotides) non-coding RNA molecules that mediate gene expression. This is an important regulatory mechanism to modulate fundamental cellular processes such as differentiation, proliferation, death, metabolism, and pathophysiology of many diseases. The miRNA expression profile of the kidney differs greatly from that of other organs, as well as between the different regions in the kidney. In kidneys, miRNAs are indispensable for development and homeostasis. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
147
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(154 citation statements)
references
References 188 publications
4
147
0
3
Order By: Relevance
“…The dysregulation of miRNAs results in various disease states, including renal dysfunction and injury (6)(7)(8). In recent studies, we (9-11) and others (12)(13)(14) found that miRNAs can be secreted by cells into body fluids and these circulating miRNAs are highly stable.…”
Section: Introductionmentioning
confidence: 99%
“…The dysregulation of miRNAs results in various disease states, including renal dysfunction and injury (6)(7)(8). In recent studies, we (9-11) and others (12)(13)(14) found that miRNAs can be secreted by cells into body fluids and these circulating miRNAs are highly stable.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 The role of miRNAs in kidney diseases has been an area of intense investigation in the past several years. 9,[26][27][28][29][30][31][32] Work from our laboratory and other groups 9,26,[30][31][32] has elucidated the role of numerous miRNAs in the pathophysiology of DN. However, the in vivo functional roles of miRNAs in renal inflammation during DN are not clear.…”
mentioning
confidence: 99%
“…There are also emerging reports about microRNAs in renal field. Several comprehensive reviews of microRNAs research on kidney development, function, and diseases have been previously published [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. This review will focus on the current research progress of microRNAs in diabetic kidney disease.…”
Section: Micrornasmentioning
confidence: 99%